2014
DOI: 10.1007/s00240-014-0704-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Randall’s plaque as an in vitro model system for studying the role of acidic biopolymers in idiopathic stone formation

Abstract: Randall’s plaque (RP) deposits seem to be consistent among the most common type of kidney stone formers, idiopathic calcium oxalate stone formers. This group forms calcium oxalate renal stones without any systemic symptoms, which contributes to the difficulty of understanding and treating this painful and recurring disease. Thus, the development of an in vitro model system to study idiopathic nephrolithiasis, beginning with RP pathogenesis, can help in identifying how plaques, and subsequently stones, form. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…They added poly-L-aspartic acid to the CP solution, and observed multi-laminated CP spherules formed through the PILP pathway by SEM. These spherules were striking resemble kidney stones, which give some clues that PILP could be a necessary process of kidney stone formation (Chidambaram et al, 2015;Lovett et al, 2019;O'Kell et al, 2019).…”
Section: Calcium Phosphatementioning
confidence: 94%
“…They added poly-L-aspartic acid to the CP solution, and observed multi-laminated CP spherules formed through the PILP pathway by SEM. These spherules were striking resemble kidney stones, which give some clues that PILP could be a necessary process of kidney stone formation (Chidambaram et al, 2015;Lovett et al, 2019;O'Kell et al, 2019).…”
Section: Calcium Phosphatementioning
confidence: 94%
“…Nephrolithiasis is a highly recurring disease and prevention of stone recurrence during treatment process is as important as the treatment itself [25,26]. The study showed that 79.3% of male patients and 80.0% of female patients have kidney stone formation recurrence ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The polymer used in the PILP process, referred to as the process directing agent, was usually polyaspartate but similar anionic polyelectrolytes were also used [242,243]. Model systems were devised for biomimetic mineralization of collagen sponges [241,244,245] and models of bone [42,241,242,246], tendon [247], dentin [248] and soft tissues [249][250][251][252].…”
Section: Mineralization In the Extracellular Matrix Of Collagenous Hard Tissuesmentioning
confidence: 99%
“…Biomimetic studies of collagen mineralization were also been made with OPN [41,159,[250][251][252][253][254] and interpreted as due to the PILP mechanism. A comparative study showed that collagen mineralization using solutions containing OPN was more homogeneous, rapid and reproducible than with polyaspartate [159].…”
Section: Mineralization In the Extracellular Matrix Of Collagenous Hard Tissuesmentioning
confidence: 99%